Narcisismo discursivo e metaficção em Lobo Antunes: uma leitura de Não entres tão depressa nessa noite escura - Navas, Diana (2007)
The present study proposes to verify how the confluence of the lyric and epic genres happens in the novel Não entres tão depressa nessa noite escura, of António Lobo Antunes, as well as to show what, in fact, configures its poeticity. Initiating with the exposition of the path that has been followed by the contemporary Portuguese romance and, afterwards, reflecting briefly on the works of fiction written by Lobo Antunes so far, as well as on the biographical and structural traits present in his works, the present studies culminates with the analysis of the novel. Having as a central hub the work carried out by Lobo Antunes with and through the language, the research aims to demonstrate how the novel in question is, according to the concepts developed by Linda Hutcheon, a metafiction, that is, a work that alerts us to its own construction process, or even, to a kind of discursive narcissism. Pointing out to the fact that the work with the language is, at the same time, the central theme of the novel and also the basic principle of its construction, this study shows how Lobo Antunes s novel, a novel in process, evidences its scriptural poiesis, escapes from the rigid classifications of the traditional forms of literary narrative, pioneering a new form of narrating, or even, a new conception of narrative genre, once that in it the lyric and epic genres conjugating themselves and thus merging themselves. With the analysis of this novel, the present study also aims to demonstrate how, always through the language, Lobo Antunes s novel points to a portrait of the contemporary man and world: a multiple, fragmented, in splinters portrait, whose pieces make part of a persistent effort of desconstrucion/ reconstruction, always in the search of a possible rescue of a hypothetic lost totality